Hubungan Risiko Kontaminasi Sarana Air Bersih Dan Kualitas Bakteriologis Air Dengan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Liang Anggang - Mela Andriyani; Noraida Noraida; Rahmawati Rahmawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
In Indonesia, the number of diarrhea sufferers in 2017 was 4,274,790 patients and in 2018 there were 4,504,524 sufferers. South Kalimantan is ranked 16th out of 34 provinces with a prevalence of diarrhea cases of 8.6%. This study aims to determine the relationship between the risk of contamination of clean water facilities and the bacteriological quality of water with the incidence of diarrhea in children under five in the working area of Puskesmas Liang Anggang. This type of research is an analytical observational case-control design with a retrospective approach. Comparison of case samples with controls 1:1. The case samples were 42 samples so that the total sample was 84 children. Data analysis using chi-square test. The highest results were obtained, namely at a low risk of contamination as much as 50% and those that did not meet the bacteriological quality requirements as much as 59.5%. The results of statistical tests showed that there was no relationship between the risk of contamination of clean water facilities and the incidence of diarrhea in children under five (p 0.827 > 0.05) and there was no relationship between the bacteriological quality of water and the incidence of diarrhea in children under five (p 0.120 > 0.05). For further researchers to be able to examine other factors with a larger sample and a wider scope so as to increase the accuracy of research results.